Skeletal maturation substantially affects elastic tissue properties in the endosteal and periosteal regions of loaded mice tibiae. (15th July 2015) - Checa, Sara; Hesse, Bernhard; Roschger, Paul; Aido, Marta; Duda, Georg N.; Raum, Kay; Willie, Bettina M.
Graphical abstract: Abstract: Although it is well known that the bone adapts to changes in the mechanical environment by forming and resorbing the bone matrix, little is known about the influence of mechanical loading on tissue material properties of the pre-existing and newly formed bone. In this study, we analyzed the newly formed and pre-existing tissue after two weeks of controlled in vivo axial compressive loading in tibia of young (10 week-old) and adult (26 week-old) female mice and compared to the control contralateral limb, by means of scanning acoustic microscopy. Additionally, we used quantitative backscattered electron imaging to determine the bone mineral density distribution within the newly formed and pre-existing bone of young mice. No significant differences were found in tissue stiffness or mineral density in the pre-existing bone tissue as a result of external loading. In the endosteal region, 10 and 26 week loaded animals showed a 9% reduction in bone tissue stiffness compared to control animals. An increase of 200% in the mineral apposition rate in this region was observed in both age groups. In the periosteal region, the reduction in bone tissue stiffness and the increase in bone mineral apposition rate as a result of loading were two times higher in the 10 compared to the 26 week old animals. These data suggest that, during growth and skeletal maturation, the response of bone to mechanical loading is a deposition of new bone matrix, where the tissue amount but not its mineral or elastic properties are influenced by animal age.